TANGGUNG JAWAB NOTARIS SEBAGAI PEJABAT PEMBUAT AKTA TERHADAP AKTA YANG MENGANDUNG CACAT HUKUM - Eka Damara, I Putu; Oka Parwata, A. A. Gede (Kertha Semaya : Journal Ilmu Hukum; Vol. 03, No. 01, Januari 2015)
This paper is about responsibility as a notary deed official deed containing the legal disability. The problems that occur in practice found that the presence of a notary deed juridical disabilities. Here arises the norm ambiguity about how the responsibility of the notary deed containing the legal disability. This paper aims to grasp and understand the responsibilities of a notary deed official deed containing the legal disability. paper, using normative legal research methods to the type of legal concept analysis approach (analitical & conseptual approach). This paper presented a study that as Notary public officials who run most of the power in the field of civil law countries, especially to create an authentic deed. Notary responsible for the deed made before him that the law is flawed, or not qualified notary formal. Here have a moral responsibility as well as could be required to compensate the injured party due to negligence in the notary deed made.
Keywords: Notary, Responsibility, disability law